Development of Peer-Scaffolding-Based Learning Program to Train the Performance Assessment Ability of Prospective Science Teacher - Jalmo, Tri; Hasnunidah, Neni; Fadiawati, Noor; Priadi, Median Agus (FKIP Universitas Lampung, 2022)
The aim of the research is to develop a peer scaffolding-based learning program to equip prospective science teacher students with the ability to develop performance appraisals. This program was developed using a 4D model (Define, Design, Develop, and Disseminate), the development of which has reached the stage of feasibility testing (Develop). Data collection techniques with questionnaires to measure the validity of the feasibility of learning programs and essay tests for the ability to develop performance appraisals. The results of this study indicate that the learning program developed got an average score of 4.00 (very valid category) in all aspects of feasibility. The results of the program trial show that there is an increase in student abilities seen from their N-gain (0.41: moderate criteria). Improvement in the aspect of the ability to understand the scope of the assessment with “low” criteria (0.036), planning an assessment with “medium” criteria (0.72). Based on this, it is concluded that the program developed is quite effective in providing performance appraisal skills for prospective science teacher students.Keywords: learning program, peer scaffolding, performance assessment.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp284-293